Antibacterial and fungicidal effect of ethanol extracts from Juniperus sabina, Chamaecyparis lawsoniana, Pseudotsuga menziesii and Cephalotaxus harringtonia - Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; Zazharskyi, V. V.; Zazharsky, V. V.; Zazhzharskiy, V. V.; Зажарський, Володимир Володимирович; et al. (Oles Honchar Dnipropetrovsk National University, 2020)
We determined a high antibacterial effect of ethanol extracts of four species of gymnosperms (Juniperus sabina, Chamaecyparis lawsoniana, Pseudotsuga menziesii and Cephalotaxus harringtonia) against 23 strains of bacteria of families Enterobacteriaceae (Escherichia coli, Enterococcus faecalis, Salmonella typhimurium, S. adobraco, Proteus vulgaris, P. mirabilis, Serratia marcescens, Klebsiella pneumoniae), Staphylococcaceae (Staphylococcus aureus, S. epidermidis), Yersiniaceae (Yersinia enterocolitica), Bacillaceae (Bacillus subtilis, B. cereus), Listeriaceae (Listeria ivanovi, L. іnnocua, L. monocytogenes), Corynebacteriaceae (Corynebacterium xerosis), Campylobacteraceae (Campylobacter jejuni), Nocardiaceae (Rhodococcus equi), Pseudomonadaceae (Pseudomonas аeruginosa) and one strain of fungi of the Saccharomycetaceae family (Candida albicans). The experiment in vitro revealed zone of inhibition of growth of colonies, measuring over 8 mm, produced by ethanol extracts from J. sabina against seven species of bacteria (S. aureus, B. subtilis, B. cereus, L. іnnocua, C. xerosis, Rh. equi and P. аeruginosa), Ch. lawsoniana – against five species (E. coli, B. subtilis, L. іnnocua and Rh. equi), P. menziesii –two species (Rh. equi and P. mirabilis), C. harringtonia – ten species of microorganisms (E. coli, S. aureus, S. epidermidis, L. ivanovi, L. monocytogenes, C. xerosis, C. jejuni, P. vulgaris, S. marcescens and C. albicans). As a result of the research, the most promising plants for further in vivo study of antibacterial activity were C. harringtonia and J. sabina. Ми визначили високу антибактеріальну дію етанолових екстрактів чотирьох видів голонасінних рослин (Juniperus sabina, Chamae-cyparis lawoniana, Pseudotsuga menziesii та Cephalotaxus harringtonia) щодо 23 штамів бактерій сімейства Entero -bactericeae (Escherichia coli, Enterococuri Salinea, Enterococcus faecalis. . adobraco, Proteus vulgaris, P. mirabilis, Serratia marcescens, Klebsiella pneumoniae), Staphylococcaceae (Staphylococcus aureus, S. epidermidis), Yersiniaceae (Yer-sinia enterocolitica), Bacillaceae (Bacillusa Listeria, Listeriaceica Listeria, Master Cecella, Listeria, Ceister, Cisterna L. іnnocua, L. monocytogenes), Corynebacteriaceae (Corynebacterium xerosis), Campylobacteraceae (Campylobacter jejuni), Nocardiaceae (Rhodococcus equi), Pseudomonadaceae (Pseudomonas аeruginosa) сімейства Candidac Saceace Saceace Saceace Saceace Saceace Saceace Saceace Saceaceacea. Експеримент in vitro виявив зону пригнічення росту колоній розміром понад 8 мм, продуковану екстрактами етанолу з J. sabina проти семи видів бактерій (S. aureus, B. subtilis, B. cereus, L. іnnocua, C .xerosis, Rh. equiand P. аeruginosa), Ch. lawoniana– проти п’яти видів (E. coli, B. subtilis, L. іnnocua і Rh. equi), P. menziesii - дві види (Rh. equi та P. mirabilis), C. harringtonia - десять видів мікроорганізмів (E . coli, S. aureus, S. epidermidis, L. ivanovi, L. monocytogenes, C. xerosis, C. jejuni, P. vulgaris, S. marcescens та C. albicans). В результаті досліджень найбільш перспективними рослинами для подальшого вивчення антибактеріальної активності in vivo були C. harringtonia та J. sabina.
Антибактеріальна та фунгіцидна дія екстрактів етанолу з Juniperus sabina, Chamaecyparis lawoniana, Pseudotsuga menziesii та Cephalotaxus harringtonia
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396
Keywords: candidiasis; кандидоз; growth inhibition zone; зона гальмування росту; bacterial colonies; колонії бактерій; multi-resistant strains; мультистійкі штами; gymnosperms; голонасінні